2022
DOI: 10.3389/fped.2022.1031847
|View full text |Cite
|
Sign up to set email alerts
|

Success rate and duration of orotracheal intubation of premature infants by healthcare providers with different levels of experience using a video laryngoscope as compared to direct laryngoscopy in a simulation-based setting

Abstract: BackgroundEndotracheal intubation of very low birth weight infants (VLBWI) is an essential procedure in NICUs, but intubation experience is often limited. Video laryngoscopy (VL) has been described as a tool to improve intubation skills, but studies in high-risk neonatal populations are limited.ObjectiveThe aim of this study was to investigate whether VL is a useful tool to support airway management in high-risk premature infants with inexperienced operators.MethodsIn this crossover study predominantly inexper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Change in laryngoscope type was rare and did not increase the chance of second attempt success. Several studies have suggested benefits to VL as a training tool for less experienced neonatal staff, although evidence regarding broader settings and experience levels is less clear 7 20–22. A Cochrane systematic review of VL use in neonates reported increased success for the first attempt at TI, but no overall reduction in the number of TI attempts, with modest sample sizes and moderate to very low quality evidence 23.…”
Section: Discussionmentioning
confidence: 99%
“…Change in laryngoscope type was rare and did not increase the chance of second attempt success. Several studies have suggested benefits to VL as a training tool for less experienced neonatal staff, although evidence regarding broader settings and experience levels is less clear 7 20–22. A Cochrane systematic review of VL use in neonates reported increased success for the first attempt at TI, but no overall reduction in the number of TI attempts, with modest sample sizes and moderate to very low quality evidence 23.…”
Section: Discussionmentioning
confidence: 99%
“…Another often overlooked advantage of video laryngoscopy, not captured in a randomized trial involving experienced proceduralists like the one conducted by Rivas and colleagues ( 1 ), is its role in procedural training and coaching. By creating a real-time shared visual model between the proceduralist and other team members, video laryngoscopy has been associated with improved outcomes when used as a coaching device during intubation attempts by inexperienced operators ( 13 ), and during simulation ( 20 ). In fact, first-attempt intubation success rates among inexperienced trainees learning endotracheal intubation is significantly improved when an instructor provides real-time coaching while sharing the operator’s view on the video laryngoscope ( 21 ).…”
mentioning
confidence: 99%